Evolutionary History of Bats : Fossils, Molecules and Morphology / [electronic resource] - Gunnell, Gregg F.; Simmons, Nancy B. (Cambridge : Cambridge University Press, 2012)
Advances in morphological and molecular methods continue to uncover new information on the origin and evolution of bats. Presenting some of the most remarkable discoveries and research involving living and fossil bats, this book explores their evolutionary history from a range of perspectives. Phylogenetic studies based on both molecular and morphological data have established a framework of evolutionary relationships that provides a context for understanding many aspects of bat biology and diversification. In addition to detailed studies of the relationships and diversification of bats, the topics covered include the mechanisms and evolution of powered flight, evolution and enhancement of echolocation, feeding ecology, population genetic structure, ontogeny and growth of facial form, functional morphology and evolution of body size. The book also examines the fossil history of bats from their beginnings over 50 million years ago to their diversification into one of the most globally wide-spread orders of mammals living today.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Bats, Fossil